Synthesis, thermal conductivity, and hydrogen compatibility of a high melt point solid solution uranium carbide, (U0.2Zr0.8)C. (October 2022) - Kardoulaki, E.; White, J.T.; Williams, J.K.P.; Taylor, B.; Croell, A.; Rosales, J.; Taylor, C.A.; Widgeon Paisner, S.; Coons, T.; Byler, D.D.; Volz, M.; McClellan, K.J.
Highlights: Phase pure (U, Zr)C feedstocks were synthesized via carbothermic reduction. Samples sintered via spark plasma sintering enabled thermal property measurements. (U0.2 Zr0.8 )C0.93 thermal conductivity was measured for the first time up to 1473 K. Hydrogen compatibility testing was performed at 2600 K over a 3-hour exposure. (U, Zr)C fuels show great potential for nuclear thermal propulsion applications. Abstract: Uranium-zirconium carbides, (U, Zr)C, have been previously considered for nuclear thermal propulsion (NTP) reactors due to their high melting point, low neutron cross section, and good hydrogen compatibility. Fuel in NTP reactors would operate under extreme environments: high temperatures (∼3000 K) and under H2 exposure. Despite (U, Zr)C fuels showing promise for extreme environment operation, very little is known about their thermal conductivity as a function of temperature and their H2 compatibility at temperatures over 2500 K. In this work, phase pure Uy Zr1-y Cz with y = 0.1, 0.2, 0.3 and z = 0.8, 0.85, 0.93 was synthesized and high density (U0.2 Zr0.8 )C samples were fabricated via spark plasma sintering. The thermal diffusivity, specific heat, and thermal expansion of (U0.2 Zr0.8 )C were measured, from which the thermal conductivity up to 1473 K was calculated for the first time. Furthermore, (U0.2 Zr0.8 )C samples with different geometries were exposed to H2 at 2600 K for 3 h using the compact fuel element environmental test facility at NASA Marshall Space Flight Center. Both samples performed remarkably well under hot hydrogen attack and no macroscopic cracking was identified. The combination of the relatively high thermal conductivity of these fuels, compared to UO2 for example, which increases with temperature, and their remarkable hydrogen compatibility make them excellent candidates for NTP reactors.